5(-8m+7)-m=-4m+35

Simple and best practice solution for 5(-8m+7)-m=-4m+35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-8m+7)-m=-4m+35 equation:


Simplifying
5(-8m + 7) + -1m = -4m + 35

Reorder the terms:
5(7 + -8m) + -1m = -4m + 35
(7 * 5 + -8m * 5) + -1m = -4m + 35
(35 + -40m) + -1m = -4m + 35

Combine like terms: -40m + -1m = -41m
35 + -41m = -4m + 35

Reorder the terms:
35 + -41m = 35 + -4m

Add '-35' to each side of the equation.
35 + -35 + -41m = 35 + -35 + -4m

Combine like terms: 35 + -35 = 0
0 + -41m = 35 + -35 + -4m
-41m = 35 + -35 + -4m

Combine like terms: 35 + -35 = 0
-41m = 0 + -4m
-41m = -4m

Solving
-41m = -4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4m' to each side of the equation.
-41m + 4m = -4m + 4m

Combine like terms: -41m + 4m = -37m
-37m = -4m + 4m

Combine like terms: -4m + 4m = 0
-37m = 0

Divide each side by '-37'.
m = 0

Simplifying
m = 0

See similar equations:

| F(-2)=2x^2+7x-3 | | 5f-3f+3=10f-7 | | 16x+9=8x+33 | | -6(3x-1)=-18x-6 | | 12+4l=18-3l | | 4a^4+12a^3+16a= | | 2x+9=108 | | 5-(-f)=12 | | -6(3x-1)=-18-6 | | (4x-62)=90 | | 3(7x-6)=24 | | (x+4)=2(x-7) | | -2(3x+3)=-6x+6 | | a+5.7=-2.3 | | 12+3l=18-2l | | 4x-62=x | | 7c-5=6 | | 3x+39+5x+10=180 | | 30a^2-54a+24= | | 5k+10=10k-7 | | 4/100+1=2.2/10 | | 3x^2-15x=20 | | c=8p+25+4 | | (2x+4)=28 | | n+5=9*3 | | 4y+2=-.3(8-12y) | | (4x+60)=120 | | d-3=(13) | | x-(4x-7)=5x-x+21 | | 2x+9-6W=-19 | | -4.2+31.5=-65.1x | | -15000000x+3056890000=5550000x+2085000000 |

Equations solver categories